2012
DOI: 10.1016/j.jue.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The value of scarce water: Measuring the inefficiency of municipal regulations

Abstract: Keywords: Drought policy Increasing-block price Market-based regulation Urban water demand Water price Water restriction a b s t r a c t Rather than allowing urban water prices to reflect scarcity rents during periods of drought-induced excess demand, policy makers have mandated command-and-control approaches, primarily rationing the use of water outdoors. While such policies are ubiquitous and likely inefficient, economists have not had access to sufficient data to estimate their economic impact. Using unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(37 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…Firstly, the age of a household dictates openness to new technology [36]. The newer the home, the more likely it is to already have water-saving infrastructure [36].…”
Section: Household/building Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the age of a household dictates openness to new technology [36]. The newer the home, the more likely it is to already have water-saving infrastructure [36].…”
Section: Household/building Attributesmentioning
confidence: 99%
“…Firstly, the age of a household dictates openness to new technology [36]. The newer the home, the more likely it is to already have water-saving infrastructure [36]. The household size also influences public perception, for those who live in bigger homes may also incur larger water costs and, thus, feel more obliged to invest in water-and cost-saving technology [32].…”
Section: Household/building Attributesmentioning
confidence: 99%
“…restricting outdoor water use) to curb demand in the short run and technology standards (e.g. requiring low flow toilets) to curb demand in the long run (Mansur and Olmstead 2012). In 2018, for example, over 1000 public water suppliers in Texas instituted water use restrictions in response to ongoing drought 4 .…”
Section: Introductionmentioning
confidence: 99%
“…A basic economic principle for achieving efficiency is to set price equal to marginal cost. In the context of water supply, marginal cost includes not only the variable cost associated with providing an additional unit of water to the consumer (short-run marginal cost) but may also include the cost of expanding water supply (long-run marginal cost) and scarcity rents (Hall, 2009a;Mansur & Olmstead, 2012;Riordan, 1971). The variability of future flows will affect all components of marginal cost (short run, long run, and scarcity rents) (Riordan, 1971).…”
Section: Addressing Water Scarcity Universal Access Efficiency Andmentioning
confidence: 99%
“…Economists typically advocate using prices to balance supply and demand of a scarce resource (e.g., Chesnutt & Beecher, 1998;Dalhuisen et al, 2003;Grafton et al, 2011Grafton et al, , 2015Griffin, 2001;Hirshleifer et al, 1960;Howe & Linaweaver, 1967;Olmstead & Stavins, 2009;Renwick & Green, 2000). Mansur and Olmstead (2012) showed that using water pricing has significant potential welfare gains compared to regulation. However, since demand for water is inelastic (Arbués et al, 2003;Dalhuisen et al, 2003, among others), high prices may be necessary to balance supply and demand when water is scarce.…”
Section: Introductionmentioning
confidence: 99%